Exploring the Quenching of Bipolar Magnetic Region Tilts using AutoTAB - Jha B.K.; Sreedevi A.B.; Karak B.B.; Banerjee D. (My University, 2025)
The tilt of the bipolar magnetic region (BMR) is crucial in the Babcock–Leighton process for the generation of the poloidal magnetic field in the Sun. We extend the work of Jha et al. (2020) and analyze the recently reported tracked BMR catalogue based on AutoTAB (Sreedevi et al. 2023) from Michelson Doppler Imager (1996–2011) and Helioseismic and Magnetic Imager (2010–2018). Using the tracked information of BMRs based on AutoTAB, we confirm that the distribution of Bmax reported by Jha et al. (2020) is not because of the BMRs are picked multiple times at the different phases of their evolution instead it is also present if we consider each BMRs only once. Moreover, we find that the slope of Joy’s law (〈γ0〉) initially increases slowly with the increase of Bmax. However, when Bmax>2.5 kG, γ0 decreases. The decrease of observed γ0 with Bmax provides a hint to a nonlinear tilt quenching in the Babcock–Leighton process. © The Author(s), 2024.